2015
DOI: 10.1128/aac.04294-14
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimalarial Activity of Novel Semisynthetic Nocathiacin I Antibiotics

Abstract: b Presently, the arsenal of antimalarial drugs is limited and needs to be replenished. We evaluated the potential antimalarial activity of two water-soluble derivatives of nocathiacin (BMS461996 and BMS411886) against the asexual blood stages of Plasmodium falciparum. Nocathiacins are a thiazolyl peptide group of antibiotics, are structurally related to thiostrepton, have potent activity against a wide spectrum of multidrug-resistant Gram-positive bacteria, and inhibit protein synthesis. The in vitro growth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…498 Thus, unlike other eukaryotes, P. falciparum is sensitive to many thiopeptides such as thiostrepton, micrococcin, and GE2270, and nocathiacin. 499508 Other protein synthesis inhibitors also have demonstrated a similar anti-malarial activity. 509511 However, it should be noted that protease inhibitors are additionally known to be active against the Plasmodium parasite, as the proteasome is crucial for development.…”
Section: Thiopeptidesmentioning
confidence: 99%
“…498 Thus, unlike other eukaryotes, P. falciparum is sensitive to many thiopeptides such as thiostrepton, micrococcin, and GE2270, and nocathiacin. 499508 Other protein synthesis inhibitors also have demonstrated a similar anti-malarial activity. 509511 However, it should be noted that protease inhibitors are additionally known to be active against the Plasmodium parasite, as the proteasome is crucial for development.…”
Section: Thiopeptidesmentioning
confidence: 99%
“…Their mechanisms of action on Plasmodium have not been as well described, although a number of studies have addressed this issue. There are three categories of ribosomes in Plasmodium : mitochondrial, plastid and nuclear [ 28 ]. As suggested by three studies [ 29 31 ], tetracycline may directly inhibit mitochondrial protein synthesis and also decrease the activity of a mitochondrial enzyme (i.e., dihydroorotate dehydrogenase) involved in de novo pyrimidine synthesis [ 32 ].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Doxycycline at a dose of 100 mg/day starting at the day of arrival in endemic areas and continuing for up to 4 weeks after returning, still remains highly effective as P. falciparum prophylaxis. Concerning the treatment of malaria, studies conducted in the 1950s [ 28 , 39 ] and in 1970 [ 40 , 41 , 66 , 67 ] have shown the effectiveness of cycline monotherapy in treating simple access to P. falciparum . Later, the need for a minimum 7-day treatment was demonstrated; the disappearance of parasites was effective only after 5 days at a dose of 200 mg daily [ 68 ].…”
Section: Clinical Effectivenessmentioning
confidence: 99%
“…A water-soluble derivative of nocathiacin exerted an irreversible growth inhibition within the first growth cycle at a nanomolar range against chloroquine-susceptible and resistant P. falciparum strains and was immediately effective [120]. Further investigations need to be done on this drug and its derivatives to understand its mode of action P. falciparum .…”
Section: Thiopeptides: Thiostrepton and Nocathiacinmentioning
confidence: 99%